VERBA BERVALENSI TIGA ZHANNA WA AKHWÄ€TUHAÄ€ KAJIAN MORFOSINTAKSIS - Arifuddin, Hanik Arwanah (Arabic Letters and Department, 2015)
Transitive or intransitive verbs have semantic characteristics. The semantic characteristics determine the valence verbs. Valence verbs are the verb ability to be accompanied by an argument in a sentence. Zhanna wa akhwÄtuhÄ verbs have three arguments: first argument (Subject), second argument (O1), and third argument (O2). The purposes of this study are describing the shape, function, and three-valent verbs case zhanna wa akhwÄtuhÄ with the arguments.The data used in this study are sentences and clauses containingzhanna wa akhwÄtuhÄ. The data source are taken from book Aâ€™n-Nahwul-WÄfÄ« by Abbas Hasan, Aâ€™n-Nachwul-â€˜ArabÄ« by Ibrahim Ibrahim Barakat, and Syarch Ibnu â€˜AqÄ«l by Bahauddin Abdullah bin 'Aqil Al-'Aqli Al Mishri Al-Hamdani. The researcher uses data collection methods referring to written data with tapping technique as basic technique and noted technique as advanced technique. The data analysis used distributional method with disappeared technique as following technique. The results of this research are as follows: (1) Zhanna wa akhwÄtuhÄ verbs have derivated and non derivated forms. (2) All of the data are verbal sentences (jumlah fi'liyyah) with perfect, imperfect, and imperatives verbs. (3) The function of zhanna wa akhwÄtuhÄ verbs include S-P-O1-O2. (4) The case of three-valent verbs zhanna wa akhwÄtuhÄÂ and the surrounding arguments are active, agentive, and objective.